Immune-regulating effects of exercise on cigarette smoke-induced inflammation - Madani A; Alack K; Richter MJ; Krüger K (Dove Medical Press, 2018)
Ashkan Madani,1 Katharina Alack,2 Manuel Jonas Richter,3,4 Karsten Krüger1 1Department of Exercise and Health, Institute of Sports Science, Leibniz University Hannover, Germany; 2Department of Sports Medicine, University of Giessen, Germany; 3Department of Internal Medicine, Justus Liebig University Giessen, Universities of Giessen and Marburg Lung Center (UGMLC), Germany; 4German Center for Lung Research (DZL), Giessen, Germany Abstract: Long-term cigarette smoking (LTCS) represents an important risk factor for cardiac infarction and stroke and the central risk factor for the development of a bronchial carcinoma, smoking-associated interstitial lung fibrosis, and chronic obstructive pulmonary disease. The pathophysiologic development of these diseases is suggested to be promoted by chronic and progressive inflammation. Cigarette smoking induces repetitive inflammatory insults followed by a chronic and progressive activation of the immune system. In the pulmonary system of cigarette smokers, oxidative stress, cellular damage, and a chronic activation of pattern recognition receptors are described which are followed by the translocation of the NF-kB, the release of pro-inflammatory cytokines, chemokines, matrix metalloproteases, and damage-associated molecular patterns. In parallel, smoke pollutants cross directly through the alveolus–capillary interface and spread through the systemic bloodstream targeting different organs. Consequently, LTCS induces a systemic low-grade inflammation and increased oxidative stress in the vascular system. In blood, these processes promote an increased coagulation and endothelial dysfunction. In muscle tissue, inflammatory processes activate catabolic signaling pathways followed by muscle wasting and sarcopenia. In brain, several characteristics of neuroinflammation were described. Regular exercise training has been shown to be an effective nonpharmacological treatment strategy in smoke-induced pulmonary diseases. It is well established that exercise training exerts immune-regulating effects by activating anti-inflammatory signaling pathways. In this regard, the release of myokines from contracting skeletal muscle, the elevations of cortisol and adrenalin, the reduced expression of Toll-like receptors, and the increased mobilization of immune-regulating leukocyte subtypes might be of vital importance. Exercise training also increases the local and systemic antioxidative capacity and several compensatory mechanisms in tissues such as an increased anabolic signaling in muscle or an increased compliance of the vascular system. Accordingly, regular exercise training seems to protect long-term smokers against some important negative local and systemic consequences of smoking. Data suggest that it seems to be important to start exercise training as early as possible. Keywords: physical activity, pulmonary system, muscle wasting, lymphocytes, tobacco, airway epithelial cells